Analisis Yuridis Keterangan Saksi Korban dalam Perkara Tindak Pidana Persetubuhan Disertai Ancaman Kekerasan: Studi Perkara No. LP/B/02/I/2025/SPKT/Polres.Inhil - Mariano Mariano; Vivi Arfiani Siregar; KMS. Novyar Satriawan Fikri (MAN 4 Kota Pekanbaru, 2026)
This study analyzes the legal position of a victim’s testimony as evidence in criminal cases of sexual intercourse accompanied by threats of violence under Indonesian criminal law and examines its application in Case File Number: LP/B/02/I/2025/SPKT/Polres.Inhil. Using normative legal research with statutory, conceptual, and case approaches, the study finds that a victim’s testimony is valid evidence under Article 184 of the Indonesian Criminal Procedure Code (KUHAP) and plays an important role in proving the offense. However, pursuant to Article 183 KUHAP, it cannot solely justify a conviction and must be supported by other lawful evidence. In the examined case, the victim’s testimony was reinforced by visum et repertum, witness statements, and physical evidence. The investigation nevertheless faced challenges, including the victim’s psychological trauma, the absence of eyewitnesses, and delayed reporting. Therefore, professional, objective, and victim-centered investigations are essential to ensure legal certainty, justice, and protection for victims.